Carbon footprint of the Brazilian diet - Garzillo, Josefa Maria Fellegger; Machado, Priscila Pereira; Leite, Fernanda Helena Marrocos; Steele, Euridice Martinez; Poli, Vanessa Fadanelli Schoenardie; Louzada, Maria Laura da Costa; Levy, Renata Bertazzi; Monteiro, Carlos Augusto (Revista de Saúde Pública, 2021)
OBJECTIVE: To estimate the carbon footprint of the Brazilian diet and of sociodemographic strata of this population. METHODS: Carbon footprint of the diet was estimated based on data from two 24-hour diet records, obtained in 2008 and 2009, from a probabilistic sample of the Brazilian population aged 10 years and over (n = 34,003) and on environmental impact coefficients of food and culinary preparations consumed in Brazil (gCO2e/kg). Means with 95% confidence intervals of food consumption (kcal/person/day) and the carbon footprint of the diet (gCO2e/person/day and in gCO2e/2,000kcal) were calculated for the population as a whole and for strata according to sex, age, income, education, macro-regions and Federative Unit. Linear regression models were used to identify significant differences (p < 0.05) in the dietary carbon footprint of different sociodemographic strata. RESULTS: The average carbon footprint of the Brazilian diet was 4,489gCO2e/person/day. It was higher for males, for the age group from 20 to 49 years and for the North and Midwest regions, and tended to increase with income and education. The pattern of association of footprint with sociodemographic variables did not change substantially with adjustment for differences in the amount of food consumed, except for a reduction in the relative excess of the footprint among males and an increase in the relative excess of the footprint in the Midwest region. CONCLUSION: The carbon footprint of the Brazilian diet exceeds by about 30% the footprint of the human diet, which could simultaneously meet the nutritional requirements of a healthy diet and the global goal of containing the increase in the planet's average temperature. The pattern of association of this footprint with sociodemographic variables can help identify priority targets for public actions aimed at reducing the environmental impacts of food consumption in Brazil.